Hubungan Kesepian dengan Kualitas Hidup Lansia yang Tinggal di Panti Pelayanan Sosial Lanjut Usia - Dyah Putri Aryati; Siti Fatimah (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
A psychological problem that often occurs in elderlies is loneliness which is a result of interactions with other individuals that turns out to be different with their expectation. Loneliness in elderlies can affect their emotional conditions, coping skills, and ultimately their quality of life. This study aimed to determine the correlation between the level of loneliness and the quality of life of elderlies at the Bojongbata Nursing Home, Pemalang. The samples of this study were selected through a non-probability sampling technique with a saturated sampling approach (total sampling). The population in this study were 86 respondents, and 46 of them were chosen to be the samples. This study employed a quantitative method with an analytical observational research design and a cross sectional approach. The measuring instrument was a questionnaire. The results showed that the average level of loneliness of the respondents were 40.65, the lowest score was 24, and the highest was 63. Meanwhile, the average score of their quality of life was 65.02, the lowest was 51, and the highest was 79. The results of data analysis with Pearson correlation resulted to  value of 0.000 <0.05 with the strength of the correlation between the level of loneliness and the quality of life of the elderlies was shown by r: -0.505 or in moderate level. There was a correlation between the level of loneliness and the quality of life of the elderlies living at Bojongbata Nursing Home, Pemalang.